2022
DOI: 10.3390/ani12192612
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Diversification in Pseudacanthicus Species (Loricariidae, Hypostominae) Revealed by Comparative Mapping of Repetitive Sequences

Abstract: Pseudacanthicus is a genus of Neotropical fish with eight valid species, in addition to numerous lineages not formally identified. It occurs along the Amazon and Tocantins River basins, in Suriname and in the Guiana shield. There are no karyotypic data in the literature for species of this genus. Here, the karyotypes of three Pseudacanthicus species (P. spinosus, P. leopardus and Pseudacanthicus sp.) were comparatively analyzed by classical cytogenetics and fluorescence in situ hybridization using 18S and 5S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 51 publications
(91 reference statements)
2
5
0
Order By: Relevance
“…Therefore, in addition to involvement in chromosomal rearrangements, we consider that the participation of 5S rDNA in transposition events and non-homologous recombination may represent plausible mechanisms to explain the dispersion of these sequences to new chromosomal sites in different populations of Ancistrus sp. 1 (2n = 38, XX/XY) and Ancistrus cirrhosus (2n = 34), similarly to what has already been described in other fish groups [ 9 , 12 , 13 , 14 , 15 , 26 , 28 ].…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Therefore, in addition to involvement in chromosomal rearrangements, we consider that the participation of 5S rDNA in transposition events and non-homologous recombination may represent plausible mechanisms to explain the dispersion of these sequences to new chromosomal sites in different populations of Ancistrus sp. 1 (2n = 38, XX/XY) and Ancistrus cirrhosus (2n = 34), similarly to what has already been described in other fish groups [ 9 , 12 , 13 , 14 , 15 , 26 , 28 ].…”
Section: Discussionsupporting
confidence: 82%
“…The occurrence of ITS is suggestive of fusions [ 12 ]; however, in the analysis carried out previously [ 9 ] and in the present study, ITS was not found in any karyotype of the analyzed samples. Alternatively, the occurrence of these rearrangements has been corroborated to the detriment of the absence of ITS due to the accumulation of other groups of repetitive sequences in unstable sites prone to DBS, which may explain the occurrence of these rearrangements in these karyotypes [ 9 , 13 , 26 , 28 , 37 ]. Furthermore, the absence of ITS in rearranged karyotypes is commonly related to the loss of these sequences during fission/fusion events or the degeneration of these interstitial sites throughout the evolution of karyotypes [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations